Emotions are temporal interpersonal systems. (October 2017) - Butler, Emily A
Highlights: A description of temporal interpersonal emotion systems (TIES) is given. Models of TIES are summarized. Evidence that TIES matter beyond emotion levels is reviewed. Connections between TIES, relationship quality and emotion regulation is reviewed. Challenges and directions for future research are proposed. Abstract : Several characteristics of emotions are that they: first, evolve dynamically over time, second, extend beyond the individual to incorporate multiple people, and third, function as a system. In other words, emotions can be seen as temporal interpersonal systems. This review summarizes current models for temporal interpersonal emotion systems (TIES), evidence they matter beyond levels of emotional responding, their connections with relationship quality and interpersonal regulation, and some of the challenges for studying them. Important directions for future research include distinguishing between different patterns of interpersonal emotional dynamics and extending theory and experimental work to uncover mechanisms for altering harmful TIES and promoting beneficial ones.